High-Performance COTS FPGA SoC for Parallel Hyperspectral Image Compression With CCSDS-123.0-B-1 - Tsigkanos, Antonis; Kranitis, Nektarios; Theodoropoulos, Dimitris; Paschalis, Antonios (IEEE transactions on very large scale integration (VLSI) systems, 2020)
Nowadays, hyperspectral imaging is recognized as a cornerstone remote sensing technology. Next generation, high-speed airborne, and space-borne imagers have increased resolution, resulting in an explosive growth in data volume and instrument data rate in the range of gigapixel per second. This competes with limited on-board resources and bandwidth, making hyperspectral image compression a mission critical on-board processing task. At the same time, the "new space" trend is emerging, where launch costs decrease, and agile approaches are exploited building smallsats using commercial-off-the-shelf (COTS) parts. In this contribution, we introduce a high-performance parallel implementation of the CCSDS-123.0-B-1 hyperspectral compression algorithm targeting SRAM field-programmable gate array (FPGA) technology. The architecture exploits image segmentation to provide the robustness to data corruption and enables scalable throughput performance by leveraging segment-level parallelism. Furthermore, we exploit the capabilities of a COTS FPGA system-on-chip (SoC) device to optimize size, weight, power, and cost (SWaP-C). The architecture partitions a hyperspectral cube stored in a DRAM framebuffer into segments, compressing them in parallel using a flexible software scheduler hosted in the SoC CPU and several compressor accelerator cores in the FPGA fabric. A 5-core implementation demonstrated on a Zynq-7045 FPGA achieves a throughput performance of 1387 Msamples/s [22.2 Gb/s at 16 bits per pixel per band (bpppb)] and outperforms previous implementations in equivalent FPGA technology, allowing seamless integration with next-generation hyperspectral sensors.